Digitalization for decarbonization: Evidence from Bangladesh, the Republic of Korea, and Sri Lanka - Eleanor Hadland; Yesim Elhan-Kayalar (Asian Development Bank Institute (ADBI), 2024)
Maritime industry transports over 90% of traded cargo annually and accounts for 3% of global greenhouse gas (GHG) emissions. The Asia and the Pacific region process 64% of global cargo, has 9 of the largest 10 ports globally, and provide over 65% of seafarers employed in the industry to support global value chains. In addition to its global contributions, maritime is one of the most important industries in the region. In this paper, we investigate the impact of deploying smart solutions for facilitating port productivity, trade and decreasing GHG emissions. Using high frequency port and automatic identification system data for container vessels in 2022, we assess the technology uptake and productivity levels at 53 container ports in the Asia and the Pacific region. Then, using a speed management model, we simulate potential time and emission savings achievable at three Asian ports representing various levels of smart technology solutions in their operations: Busan (high), Colombo (medium), and Chittagong (low). Results suggest an inverse relationship between port productivity gains and technology uptake, with those ports at lower uptake levels showing higher marginal gains from introduction of smart speed management systems for vessels. Second, based on the established relationship between ship speed and fuel consumption, we investigate GHG emissions impact of smart speed management systems. This study helps demonstrate with real-time port and vessel traffic data the promising potential of digital technology solutions for greener and more efficient maritime operations with regional and global benefits.
Keywords: R41; Q56; Q53; Q52; 330; ports; smart ports; greenhouse gas emissions; digitalization; AIS